2012
DOI: 10.1523/jneurosci.3408-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Specific CREB Target Gene Induction in Human Neocortical Epilepsy

Abstract: Epilepsy is a disorder of recurrent seizures that affects 1% of the population. To understand why some areas of cerebral cortex produce seizures and others do not, we identified differentially expressed genes in human epileptic neocortex compared to nearby regions that did not produce seizures. The transcriptome that emerged strongly implicates MAP kinase signaling and CREB-dependent transcription, with 74% of differentially expressed genes containing a cyclic AMP response element (CRE) in their proximal promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
130
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 55 publications
(77 reference statements)
8
130
0
Order By: Relevance
“…For example, inducible cAMP early repressor (ICER) has been suggested to play a role in epileptogenesis as it suppresses kindling (Kojima et al 2008;Porter et al 2008). Other candidates include cAMP response element (CREB), controlling differential expression of genes in human epileptic cortex (Beaumont et al 2012), and repressor element-1 silencing transcription factor (NRSF) shown to repress epileptogenesis in a kindling model and reported to regulate target genes relevant for neuronal network remodeling in kainate-induced SE (Hu et al 2011;McClelland et al 2014).…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…For example, inducible cAMP early repressor (ICER) has been suggested to play a role in epileptogenesis as it suppresses kindling (Kojima et al 2008;Porter et al 2008). Other candidates include cAMP response element (CREB), controlling differential expression of genes in human epileptic cortex (Beaumont et al 2012), and repressor element-1 silencing transcription factor (NRSF) shown to repress epileptogenesis in a kindling model and reported to regulate target genes relevant for neuronal network remodeling in kainate-induced SE (Hu et al 2011;McClelland et al 2014).…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…Upstream of CREB activation, several known signaling pathways are rapidly activated in response to neuronal activity (Kandel 2001; reviewed in West et al 2002), including CaMKinase IV, protein kinase A, and MAPK. We have recently observed a pattern of transcriptional activation in human brain regions where seizures start that strongly implicates sustained MAPK/CREB activation and downstream coding gene activations that could underlie layerspecific changes in synaptic architecture that makes these regions prone to seizures (Rakhade et al 2005;Barkmeier et al 2012;Beaumont et al 2012).Given that human lncRNA genes tend to be less wellconserved than protein-coding genes, and can give rise to unique transcripts not found in other species, we sought out a uniquely human system to examine activity-dependent gene expression for both coding and noncoding RNAs using a pairwise comparison of human cortical regions displaying variable degrees of epileptic activities. These brain regions were removed as part of surgical treatment for intractable seizures.…”
mentioning
confidence: 99%
“…The paired analysis of high-and low-spiking neocortex within each patient is also critical to isolate the variable under study, which is the degree of activity. Total RNA was prepared using a modification of the protocol described previously (Beaumont et al 2012). The difference was that only gray matter was used by pooling two to three nearby strips of gray matter that extended from the pial surface to the white matter from each block of tissue corresponding to a given electrode location.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, GRB2 (21) and CDKN1A (22) have been reported to be upregulated in human epilepsy, and APP (23) and TGF-β (24,25) were found to be upregulated following epileptic seizures in rat a model, based on DNA microarrays. Compared with wild-type mice, RT-qPCR has shown that the mRNA expression of VEGF is 1.44-fold higher in the hippocampus of VEGF Receptor-2 (Flk-1)-overexpressing mice, characterized by an elevated threshold for seizure induction (26).…”
Section: Discussionmentioning
confidence: 99%